Theological Review for Tambak Development of Batak Toba Community - Theresia Tiodora Sitorus; Jamin Tanhidy; Stuart Guild (Asosiasi Ahli Filsafat Keilahian Indonesia, 2021)
Building and moving ponds or ancestral graves in the Toba Batak community, who have become Christians, is still practised today. The practice of building ponds is, of course, contrary to God's word, for that it needs to be responded to theologically and is the goal of this research. The method used is a descriptive qualitative method by reviewing the literature related to the research topic and reporting the findings in a description. The study results are as follows: First, building a pond with the motivation of asking for blessings from the ancestors is an act of sin. The gift of both physical and spiritual life comes from God and not the spirits of the ancestors. Second, moving and caring for ponds is wrong to prevent sickness and family quarrels because Christ bore all curses and diseases on the cross. Third, building a pond as a tribute to parents is wrong. The fifth commandment in Exodus 20:12 concerns respect for parents. It cannot be opposed to supporting the practice of building ponds. The substance of this verse is not only related to relations between humans but concerns God's blessing for His people to glorify God, the Creator, not ancestral spirits.